2014
DOI: 10.1177/0961203314560204
|View full text |Cite
|
Sign up to set email alerts
|

Lupus erythematosus tumidus: a clinical and histological study of 25 cases

Abstract: LET is a variant of CLE that has distinctive clinical, histologic and prognostic features. Unlike the patients in the case series previously described in the literature, most of our patients required treatment with antimalarials. Histology revealed mild epidermal alterations in a significant percentage of patients. Thus, in our opinion, the absence of microscopic epidermal alterations is not constant in LET.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 11 publications
(34 reference statements)
2
29
0
2
Order By: Relevance
“…Accordingly, there are no data on the performance of rather unusual entities such as lupus tumidus, which is also rarely associated with SLE. [14][15][16] Similarly, the list of neuropsychiatric symptoms was expanded, and some of the other definitions were slightly modified.…”
Section: Sle Classification-the Acr and The Slicc Criteriamentioning
confidence: 99%
“…Accordingly, there are no data on the performance of rather unusual entities such as lupus tumidus, which is also rarely associated with SLE. [14][15][16] Similarly, the list of neuropsychiatric symptoms was expanded, and some of the other definitions were slightly modified.…”
Section: Sle Classification-the Acr and The Slicc Criteriamentioning
confidence: 99%
“…One of the described patients did not smoke, the other one stopped 3 years earlier. In LETpatients, ANAs are negative, and our patients were not different; according to Kuhn et al, they are confirmed only in 10% of patients [4,11]. The literature includes contradictory reports regarding the connection between lupus erythematosus and neoplasms.…”
Section: Discussionmentioning
confidence: 46%
“…For ACLE, a total of 234 courses of AM use reported in two studies yielded an overall response rate of 91% (95% CI 87–93), with no heterogeneity ( P = 0·88, I 2 = 0%). For ICLE, the overall response rate was 68% (95% CI 56–78) with significant heterogeneity ( P = 0·01, I 2 = 61%) based on 145 courses of AM use reported in nine studies . For chilblain lupus, the cutaneous response was assessed in three studies, yielding a total of 58 courses of AMs.…”
Section: Resultsmentioning
confidence: 99%